Penerapan Metode Discovery Learning dalam Meningkatkan Aktivitas dan Hasil Belajar Al-Qur’an dan Hadits Bagi Siswa Madrasah Aliyah Negeri Aceh Besar - Rosmawar Rosmawar (2021)
The purpose of this classroom action research is to increase the activities and learning outcomes of Al-Quran Hadith on the Authenticity of the Al-Quran through the application of the Discovery Learning model. This research was conducted at MAN 2 Aceh Besar. The research was carried out for 3 months, February-April 2019. The data sources came from students of class X-IPS 2 in the odd semester of the 2018/2019 academic year. The number of students is 18 students. There are 11 male students and 7 female students. Data collection tools in the form of test items and student activity instrument sheets. Data validation is done by entering student test scores into the list of values that have been prepared previously and data validation for the observation sheet is done by ticking the prepared observation sheet. The research procedure consisted of two cycles. Each cycle consists of planning, implementation, observation and reflection. The results of the pre-cycle research were 44.4% with an average value of 69.7, while in Cycle I it was 66.7% with an average value of 75 and while in Cycle II the percentage of completeness reached 100% with an average value of 79.7. The application of Discovery Learning has gradually been able to increase student learning activities, so that it has a very significant impact on improving student learning outcomes.